Central nervous system infections associated with neurologic devices. Issue 3 (June 2021) - Bloch, Karen; Hasbun, Rodrigo
Abstract : Purpose of review: To review recent data on the epidemiology, microbiology, diagnosis, and management of central nervous system (CNS) infections associated with neurologic devices. Recent findings: The increasing use of implanted neurologic devices has led to an increase in associated infections. Cerebrospinal fluid (CSF) inflammation may be present after a neurosurgical procedure, complicating the diagnosis of CNS infection. Newer biomarkers such as CSF lactate and procalcitonin show promise in differentiating infection from other causes of CSF inflammation. Molecular diagnostic tests including next-generation or metagenomic sequencing may be superior to culture in identifying pathogens causing healthcare-associated ventriculitis and meningitis. Summary: Neurologic device infections are serious, often life-threatening complications. Rapid recognition and initiation of antibiotics are critical in decreasing morbidity. Device removal is usually required for cure.